The river murders [videorecording (DVD)] - Cowan, Richard M.; Liotta, Ray; Rhames, Ving, 1961-; Slater, Christian (Sony Pictures Home Entertainment, 2011)
A homicide detective's past comes back to haunt him when his ex-girlfriends become the target of a serial killer who's out to destroy him.